KEBIJAKAN AMERIKA SERIKAT DALM MENGIRIM PMC (PRIVATE MILITARY COMPANY) KE IRAK TAHUN 2011 - Zudma, Farras Abdu; Saeri, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is trying to explain about the policy of United States of America that send a Private Military Company to Iraq in 2011. United States is the country that has invaded Iraq in 2003 since begining until the end of the war united state has use a Private Military Company to help and make a contribute for the war in Iraq.This research is using realism perspective,realism is a perspective that explain about the national security concern in the world of anarchy international politics.This research is also using national interest theory which is explain why national sustainability matters.Private Military Company was involved in much operation freedom in Iraq, because they are hire by United State of America itself ,even after that invaded lot of army from United State was going back to America and taking demilitarization in their homeland but not for the Private Military Company it’s because United State still need their bargaining in Iraq and they need something that can be useful later.Preventif action that United State made to Iraq, after the invaded was one of the scenario that united state ever made, because there is still other reason for United State to make a policy and it should be something useful and after the invaded United State made a decision to recovery and reconstruction for Iraq it is one of the reason why United State of America send a contractor or Private Military Company in Iraq.Keyword: Private Military Company, ratified, hegemony, national interest, foreign policy, violate, superiority